PERLINDUNGAN HUKUM BAGI PEKERJA YANG TERKENA PEMUTUSAN HUBUNGAN KERJA SEPIHAK OLEH PERUSAHAAN SAAT CUTI HAMIL DI KOTA BANDUNG - Jauhari, Muhammad Yahya; Waluyo, Waluyo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This study aims to determine the form of legal protection for workers affected by the termination of the same work relationship by the company while on maternity leave in the city of Bandung and to find out how workers' rights are while on maternity leave. This study uses normative juridical by combining statutory approaches, conceptual approaches, analytical approaches, and case approaches. Sources of data obtained from legislation, books, scientific journals, court decisions, and data analysis literature and use a qualitative approach. The results of the study can be concluded that the fulfillment of maternity leave rights for female workers in the provisions of Article 82 paragraph (1) of Law Number 13 of 2003 concerning Manpower contains regarding the regulation of maternity leave for female workers who are in the pregnancy phase, that protection for workers affected by termination by the company While on maternity leave it has been stated in law number 13 of 2003 which was added to law number 11 of 2020 concerning work copyright, as well as law number 2 of 2004 which explains in the law how employers or companies must treat their employees who while on maternity leave without terminating the employment relationship unilaterally due to maternity leave. As for efforts that can be taken when workers are subject to termination of employment unilaterally, efforts can be made, namely, bipartite, conciliation, mediation, arbitration, industrial relations courts